If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -6b = -15 + 6b + -8b Combine like terms: 6b + -8b = -2b 5 + -6b = -15 + -2b Solving 5 + -6b = -15 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. 5 + -6b + 2b = -15 + -2b + 2b Combine like terms: -6b + 2b = -4b 5 + -4b = -15 + -2b + 2b Combine like terms: -2b + 2b = 0 5 + -4b = -15 + 0 5 + -4b = -15 Add '-5' to each side of the equation. 5 + -5 + -4b = -15 + -5 Combine like terms: 5 + -5 = 0 0 + -4b = -15 + -5 -4b = -15 + -5 Combine like terms: -15 + -5 = -20 -4b = -20 Divide each side by '-4'. b = 5 Simplifying b = 5
| x^2+6x+81= | | 6x+15=4x+7 | | -5(v+3)+2v+5=5v+8 | | -4(-6a-1)=100 | | X^2-2y^2=0 | | y=-2x^3+5x^2+2x-5 | | 4g+3(-4+4g)=1-g | | 6x+(x+5)=189 | | x^3+2x-2= | | f(x)=-2x^3+5x^2+2x-5 | | 12x^2+16x=3 | | 4(w-5)-2(w+1)=3(1-w) | | X+(2x-75)=90 | | (6-y^5)(6+y^5)= | | -22=3+5u | | 1/2+(2/3/3/4)-(4/5*5/6)= | | -4(4+6b)=80 | | 5z^3-15z^2-1520z=0 | | 2.9=6.9-0.8x | | 3m-3-5=-20 | | 35t=50t-37.5 | | (6xy^2-xy)(6xy^2+xy)= | | 4(y+1)=-6 | | x^2-2x+10=y | | 5x+2x-5=44 | | 7t^3-21t^2-2926t=0 | | 9+5x=4x+12 | | -4+5w=-14 | | 8x+9x-52=104-9x | | -(x-8)=3(-3x+4) | | 8=Xsquared-5x+8 | | 120+30m=80+50m |